Modulation of the in vivo inflammatory response by pro-versus anti-inflammatory intervertebral disc treatments - Cunha, C (2020)
Inflammation is central in intervertebral disc (IVD) degeneration/regeneration mechanisms, and its balance is crucial to maintain tissue homeostasis. This work investigates the modulation of local and systemic inflammatory response associated with IVD degeneration/herniation by administration of PRO-versus ANTI-inflammatory treatments. Chitosan/poly-¿-glutamic acid nanocomplexes, known as pro-inflammatory (PRO), and soluble diclofenac, a non-steroidal anti-inflammatory drug (ANTI), were intradiscally administered in a rat IVD injury model, 24 h after lesion. Two weeks after administration, a reduction of disc height accompanied by hernia formation was observed. In the PRO-inflammatory treated group, IL-1ß, IL-6 and COX-2 IVD gene expression were upregulated, and loss of nucleus pulposus (NP) structure and composition was observed. Systemically, lower T-cell frequency was observed in the lymph nodes (LN) and spleen (SP) of the PRO group, together with an increase in CD4+ T cells subset in the blood (BL) and LN. In contrast, the ANTI-group had higher proteoglycans/collagen ratio and collagen type 2 content in the NP, while an increase in the frequency of myeloid cells, M1 macrophages and activated macrophages (MHCII+) was observed at the systemic level. Overall, this study illustrates the dynamics of local and systemic inflammatory and immune cell responses associated with intradiscal therapies, which will contribute to designing more successful immunomodulatory treatments for IVD degeneration.